2014 IEEE International Electric Vehicle Conference (IEVC) 2014
DOI: 10.1109/ievc.2014.7056144
|View full text |Cite
|
Sign up to set email alerts
|

European electric vehicle fleet: driving and charging data analysis

Abstract: The electrification of the light vehicle fleets would be a reality in the coming decades. It is being studied through pilot experiences and surveys, how this change in the technology would affect the users driving behaviour. Obviously, new challenges appear, for instance the battery charging, which would be certainly different to the current needs and timings for filling up the internal combustion engine vehicles tanks. Analysis of real electric vehicle usage data is a key point in the development of the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Between 2011 and 2013 data about driving and EV demand patterns were collected on a study conducted in Europe [9]. More than 230,000 charges have been registered.…”
Section: Charging Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2011 and 2013 data about driving and EV demand patterns were collected on a study conducted in Europe [9]. More than 230,000 charges have been registered.…”
Section: Charging Behaviourmentioning
confidence: 99%
“…To ensure that each user always has sufficient charge to make the trips, it was considered a critical battery level. Following the results of [9] this value is set to 20%. Whenever a user reaches a level lower than this, regardless of the trip, the car must be charged.…”
Section: Charging Decisionsmentioning
confidence: 99%
“…A few related studies evaluated the general ability of EV fleet for power system operation, collected or surveyed large-scale EV charging data through demonstration projects, and analyzed the charging duration and amount of EVs [11][12][13][14]. However, to the knowledge of the authors, there are no reported studies evaluating the flexibility of EVCs with a valid formula that reflects EVC-data-driven characteristics, especially in a typical demand side resource perspective for grid network security.…”
Section: Introductionmentioning
confidence: 99%
“…Time to start charging at home, work, and other locations (extracted and revised fromCorchero et al, 2015) …”
mentioning
confidence: 99%